On literary attachment in South Africa tough love - Chapman, Michael 1945- (Routledge, 2022)
"This book reflects on the 'literary' in literature. Whether oral expression, Nobel laureates, or the rupturing event, the study adopts a style of intimacy to both its African locality and the wider Anglophone world: the world to which literature in South Africa continues to belong, albeit as a 'problem child'"--
Keywords: Literaturkritik; Literatur; Südafrika; South African literature (English) / History and criticism; South African literature / History and criticism; Littérature sud-africaine (anglaise) / Histoire et critique; Littérature sud-africaine / Histoire et critique; South African literature; South African literature (English); Criticism, interpretation, etc